Recent development on self-supported transition metal-based catalysts for water electrolysis at large current density. (March 2021) - Zhang, Xin-Yu; Yu, Wen-Li; Zhao, Jie; Dong, Bin; Liu, Chen-Guang; Chai, Yong-Ming
Highlights: Self-supported transition metal-based catalysts at high current density has been summarized. The design, test conditions and potential conversion of catalysts at large current are analyzed. The perspectives for further development of large current density-based catalysts are proposed. Abstract: Developing the cost-effective and robust large current density catalysts is vital for industrial electrocatalytic water splitting. However, most of reported successful catalysts have a small tested range and the current density is usually less than 100 mA cm −2, which is far from meeting the actual application demands. This review first summarizes the recent reported self-supported transition metal-based catalysts that can run stably at high current density. Where their catalytic performance in three important reactions of electrolytic cells: hydrogen evolution reaction (HER), oxygen evolution reaction (OER) and overall water splitting (OWS) have been introduced, respectively. Meanwhile, some design requirements, relevant test conditions and potential conversion in exploring large current catalysts have been generalized. Finally, some perspectives for further development of large current density-based electrocatalysts are proposed. This work may provide the guidance and reference for rational design and exploitation of self-supported high current density electrocatalysts, thus further promoting the large-scale application of water splitting. Graphical abstract: Image, graphical abstract